Cardiovascular disease in survivors of hematopoietic cell transplantation. Issue 4 (25th October 2013) - Armenian, Saro H.; Chow, Eric J.
<x xml:space="preserve">Abstract</x> Hematopoietic cell transplantation (HCT) is increasingly offered as a curative option for many patients with hematologic malignancies. Improvements in HCT strategies and supportive care have resulted in a growing number of long‐term survivors. However, these survivors are at an increased risk of developing long‐term debilitating chronic health conditions, including premature cardiovascular disease. These complications are more common than in the general population, and there are well‐described associations between therapeutic exposures, traditional cardiovascular risk factors, and subsequent cardiovascular disease risk. The authors present herein an overview of the current state of knowledge regarding pathogenesis and risk factors for some of the more commonly occurring cardiovascular complications after HCT, highlighting existing surveillance recommendations and future directions for research to minimize cardiovascular morbidity in these survivors. Cancer 2014;120:469–479. © 2013 American Cancer Society.